2017
DOI: 10.1186/s12913-017-2183-6
|View full text |Cite
|
Sign up to set email alerts
|

The potential of health literacy to address the health related UN sustainable development goal 3 (SDG3) in Nepal: a rapid review

Abstract: BackgroundHealth literacy has been linked to health outcomes across population groups around the world. Nepal, a low income country, experiences the double burden of highly prevalent communicable as well as non-communicable diseases. The World Health Organization (WHO) has positioned health literacy as a key mechanism to meet the health-related Sustainable Development Goal (SDG3). However, there is little known about the status of health literacy in developing countries such as Nepal. This paper aims to review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 61 publications
1
60
0
Order By: Relevance
“…Assessing affecting factors in scientific growth of countries indicated that in low-income andmiddle-income countries, scientific advancement has high correlation with economic growth, in which high-income countries accommodate just 16% of population in the world but publish 80% of scientific output 25. On the other hand, low-income countries by having 81% of population in the world, just produced 0.07 of all scientific publications in the world 25…”
Section: Discussionmentioning
confidence: 99%
“…Assessing affecting factors in scientific growth of countries indicated that in low-income andmiddle-income countries, scientific advancement has high correlation with economic growth, in which high-income countries accommodate just 16% of population in the world but publish 80% of scientific output 25. On the other hand, low-income countries by having 81% of population in the world, just produced 0.07 of all scientific publications in the world 25…”
Section: Discussionmentioning
confidence: 99%
“…One of the keys to improving health globally to meet the Sustainable Development Goals (SDGs) [ 1 ] is adoption by mothers of healthy home practices for better nutrition and illness prevention. Interventions to improve health literacy are recognized as essential for reaching the SDGs [ 2 ]. The challenge is acute in settings where access to health information is poor, educational levels are low, and traditional beliefs are strong.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of health literacy common in vulnerable populations, people with low levels of income and education, and people with a compromised health status [5,6], is associated with inadequate knowledge about the health as well as the healthcare system, poor access and utilisation of health services and also increased hospitalisation [7]. These, according to various authorities, lead to poor health outcomes and health inequalities [8 -10].…”
Section: Introductionmentioning
confidence: 99%
“…Even though, number three (3) of the Sustainable Development Goals (SDG) specifically targets health (to ensure healthy lives and to promote wellbeing at all ages), it can be seen that most of the other goals: SDG1 (No poverty), SDG2 (Zero hunger), SDG4 (Quality education), SDG8 (Decent work and economic growth), and SDG10 (Reduced inequalities) are all indirectly linked to health. SDG3 addresses maternal health, neonatal and child health, AIDS, tuberculosis, malaria and includes universal access to sexual and reproductive health services including family planning [7].…”
Section: Introductionmentioning
confidence: 99%